Outbreak by Ventilator-Associated ST11 K. pneumoniae with Co-production of CTX-M-24 and KPC-2 in a SICU of a Tertiary Teaching Hospital in Central China - Hu, Longhua; Liu, Yanling; Deng, Linqiang; Zhong, Qiaoshi; Hang, Yaping; Wang, Zengzeng; Zhan, Lingling; Wang, Liangxing; Yu, Fangyou (Frontiers in Microbiology, 2016)
The emergence of carbapenem-resistant Klebsiella pneumoniae (CRKP) often responsible for numerous hospital-associated outbreaks has become an important public health problem. From January 2013 to February 2014, a total of 41 non-duplicate K. pneumoniae isolates with carbapenem resistance, were collected at a tertiary teaching hospital in Nanchang, central China. Among 41 K. pneumoniae isolates, 28 were isolated from hospitalized patients including 19 from the patients in surgery intensive care unit (SICU) and 13 were isolated from ventilators. Twenty-four of 28 patients infected by CRKP have been submitted to mechanical ventilation using ventilator. More than 95% of the CRKP isolates were resistant to 13 antimicrobials tested.All CRKP isolates were confirmed as carbapenemase producer and were positive for blaKPC-2, with one positive for both blaKPC-2 and blaNDM-1. All carbapenemase-producing isolates harbored at least one of extended spectrum βlactamase genes tested, among which95.1% (39/41) of the tested isolates were found to harbor both blaCTX-M-24 and blaKPC-2, Of note, one isolate harbored simultaneously two carbapenemase genes (blaKPC-2 and blaNDM-1) and two ESBL genes (blaCTX-M-3 and blaTEM-104) . To the best of our knowledge, coexistence of blaKPC-2 and blaCTX-M-24 in one isolate is first reported. MLST results showed that 41 CRKP isolates belonged to 4 sequence types (STs) including ST11, novel ST1854, novel ST1855 and ST1224. PFGE results displayed 3 PFGE clusters. Thirty-eight ST11 CRKP isolates (92.7%, 38/41) including all 13 isolates from ventilators and 25 isolates from patients from 7 wards (18 from是ICU) belonged to same PFGE cluster, indicating these isolates were clonally related. Fifteen isolates have an identical undistinguished pattern (100% similarity) forming a single clonal population. Moreover, this clone was exclusively linked to the cases attended in SICU and linked to the Ventilators. Additionally, the other SICU cases were linked to closely related clones (similarity greater than 95%). These data indicated that the occurrence of a clonal outbreak associated with vetilators has been found. In conclusion, outbreak by by ventilator-associated ST11 K. pneumoniae with co-production of CTX-M-24 and KPC-2 is found in a SICU of a tertiary teaching hospital in central China.